Efficacy of mouthrinses in reducing oral SARS-COV-2 load: a review - Claudio Mendes PANNUTI; Isabella Neme Ribeiro dos REIS; Nathalia Vilela SOUZA; Maria Luisa Silveira SOUTO; Carlos Guillermo Benítez SILVA; Leticia Mello BEZINELLI; Clarisse Martins MACHADO; Giuseppe Alexandre ROMITO; Cristina Cunha VILLAR (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract Accumulated evidence has shown that the oral cavity may be an important reservoir for SARS-CoV-2. Some authors have suggested that the use of mouthrinses could reduce SARS-CoV-2 viral load in the saliva. Thus, the aim of this review was to synthesize evidence about the efficacy of mouthrinses in reducing the salivary viral load of SARS-CoV-2. 2. Nine randomized controlled trials (RCTs) have investigated the efficacy of different mouthrinses in reducing salivary SARS-CoV-2 loads. Various active ingredients have been tested in these trials: 0.5%,1% and 2% povidone-iodine, 0.2% and 0.12% chlorhexidine (CHX), 0.075% cetylpyridinium chloride (CPC), 0.075% CPC with Zinc lactate, 1% and 1.5% hydrogen peroxide (HP), 1.5% HP + 0.12% CHX and ß-cyclodextrin and citrox. The studies reported an intra-group reduction in the salivary levels of the virus, when compared with the baseline. However, the majority of these trials failed to demonstrate a significant inter-group difference between active groups and the control group relative to the decrease in salivary SARS-CoV-2 loads. Although promising, these results should be confirmed by larger trials.